Experimental and analytical studies on the seismic behavior of reinforced concrete columns with light transverse reinforcement - Tran, Cao Thanh Ngoc (2010)
Structures made up of reinforced concrete columns with light transverse reinforcement are very common in a region of low to moderate seismicity, and are the predominant structural system in Singapore. Recent post-earthquake investigations have indicated that extensive damage in reinforced concrete columns with light transverse reinforcement occurs due to excessive shear deformation that subsequently leads to shear failure, axial failure and eventually full collapse of the structures. Therefore, a thorough evaluation of reinforced concrete columns with light transverse reinforcement is needed to understand the seismic behavior of these structures. For this purpose, an experimental program carried out on reinforced concrete columns with light transverse reinforcement subjected to seismic loading is conducted. Ten 1/2-scale reinforced concrete columns with light transverse reinforcement are tested to investigate the seismic behavior of these columns. The variables in the test specimens include column axial loads, aspect ratios, and cross sectional shapes. The specimens are tested to the point of axial failure under a combination of a constant axial load and quasi-static cyclic loadings to simulate earthquake actions. Experimental results obtained include hysteretic responses, cracking patterns, strains in reinforcing bars, displacement decomposition and cumulative energy dissipation.